2023
DOI: 10.1002/anie.202300094
|View full text |Cite
|
Sign up to set email alerts
|

Concerted and Selective Electrooxidation of Polyethylene‐Terephthalate‐Derived Alcohol to Glycolic Acid at an Industry‐Level Current Density over a Pd−Ni(OH)2 Catalyst

Abstract: Electro‐reforming of Polyethylene‐terephthalate‐derived (PET‐derived) ethylene glycol (EG) into fine chemicals and H2 is an ideal solution to address severe plastic pollution. Here, we report the electrooxidation of EG to glycolic acid (GA) with a high Faraday efficiency and selectivity (>85 %) even at an industry‐level current density (600 mA cm−2 at 1.15 V vs. RHE) over a Pd−Ni(OH)2 catalyst. Notably, stable electrolysis over 200 h can be achieved, outperforming all available Pd‐based catalysts. Combined exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 59 publications
2
70
0
Order By: Relevance
“…In addition, fluorescence probe experiments were also carried out to verify the differences in the interaction between the catalysts and OH ad in the CO 2 RR (Figure K). The nonfluorescent terephthalic acid (TPA) was used as the probe to react with the •OH radical generated during the reaction to produce the fluorescent 2-hydroxyterephthalic acid . Evidently, the fluorescence intensity of Al–Cu/Cu 2 O was higher than that of Cu/Cu 2 O, indicating that oxophilic Al–Cu/Cu 2 O can promote the generation of *OH active species.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fluorescence probe experiments were also carried out to verify the differences in the interaction between the catalysts and OH ad in the CO 2 RR (Figure K). The nonfluorescent terephthalic acid (TPA) was used as the probe to react with the •OH radical generated during the reaction to produce the fluorescent 2-hydroxyterephthalic acid . Evidently, the fluorescence intensity of Al–Cu/Cu 2 O was higher than that of Cu/Cu 2 O, indicating that oxophilic Al–Cu/Cu 2 O can promote the generation of *OH active species.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Although previous work has already shown that Pd-and Au-based catalysts are well-suited for selective oxidation of EG for glycolate production, they suffer from either large operation voltage (> 1 V) or high loading density of noble metal (> 1 mg cm −2 ), which is deemed as a major hinderance to economic implementation. [31][32][33] Given this, engineering catalyst with low mass loading of noble metal to oxidize EG to glycolate under a marginal voltage will further enhance the economic viability of the electroreforming technology toward upcycling of PET plastic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, high conductivity is reflected in crystalline materials. , Therefore, combining the advantages of amorphous and crystalline materials to construct crystal-phase hetero-nanostructure is an effective strategy for enhancing the electrocatalytic activity of materials. As for the anode, Pd-based materials, as an effective electrocatalyst for the oxidation of alcohols, exhibit good catalytic performance in the electrooxidation of EG. Moreover, controlling the morphology of nanostructures is an effective method to further improve the catalytic performance of Pd-based materials. For example, high-curvature tip nanostructures can enhance the local electric field and promote the enrichment of reactants around the active sites due to the tip effect (TE) …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the market size of GA is growing with its increasing use in the daily chemicals, cosmetic products, textiles, and pharmaceutical industries, expected to reach US$531.5 million by 2027 . Fortunately, the production of GA can be achieved by controllable electrooxidation of EG derived from nondegradable PET plastic waste, promoting the value-added recycling and resource utilization of waste. , Based on these inspirations, it is feasible to construct an integrated coupled electrolysis system for converting low-value waste into high value-added chemicals by combining nitrate wastewater treatment and PET plastic waste upcycling.…”
Section: Introductionmentioning
confidence: 99%